Distal Biceps Brachii - Brigido, Monica Kalume; De Maeseneer, Michel; Morag, Yoav (Seminars in Musculoskeletal Radiology, 2013)
There has been a renewed interest in the recent literature with regard to the normal anatomy of the distal biceps tendon. Cadaveric studies have demonstrated that a large percentage of individuals have two independent muscle bellies, the short and the long head, with two distinct separate tendons attaching at the radial tuberosity. To avoid diagnostic errors that may have an impact on patient management in case of tendon injury, it is important to keep this anatomical variant in mind. Ultrasonography has been shown to be a useful imaging modality in the evaluation of disorders of the distal biceps brachii muscle and tendon. In this article, we review the relevant anatomy of the distal biceps brachii, the ultrasound technique with alternative approaches for optimum visualization of the distal tendon, and the most common pathologies in this region.
Keywords: distal; biceps; anatomy; radial tuberosity; ultrasound